The Effect of Training on Employee Performance in the Food & Beverage Department at the Stones Legian, Bali - Autograph Collection Hotels - Putra, I Dewa Gde Angga Krisna; Sulistyawati, Ni Luh Ketut Sri; Jata, I Wayan (Formosa Journal of Applied Sciences, 2024)
Effective training creates good employee performance. The purpose of this research is to determine the effect of training on employee performance in the Food & Beverage Department of The Stones Legian, Bali - Autograph Collection Hotels.  There were 80 respondents in this research using saturated sampling method. This research found that employee performance is positively and significantly affected by training. Questionnaires were distributed through data collection and measured 24 statement items with a Likert 4 scale. Classical assumption testing, simple linear regression, coefficient of determination and t-test are used in data analysis techniques in this research.  Based on the coefficient of determination analysis, it was found that training significantly influenced 70.4% of employee performance. Then other aspects that have not been included in this research also have an influence of 29.6%.